Influence Fiscal Decentralization of Poverty in Papua Province - Sarlota Ratang; Munawar Ismail; Iswan Noor; Setyo Tri Wahyudi (AIBPM Publisher, 2025)
Poverty remains one of the most persistent development challenges in Papua Province, which consistently records the highest poverty rate in Indonesia. Fiscal decentralization is expected to enhance regional autonomy and public service effectiveness through the distribution of government expenditure across priority sectors. This study aims to analyze the influence of fiscal decentralization on poverty levels in Papua Province by examining government expenditure in the infrastructure, education, health, and economic sectors. Using panel data from 29 districts and cities in Papua covering the period 2010–2021, the research employs a dynamic panel data regression approach using the Arellano–Bond GMM estimation model. The results indicate that education expenditure has a significant negative effect on poverty, with a coefficient of ?1.259, and economic expenditure also reduces poverty with a coefficient of ?0.497. In contrast, health expenditure shows a positive coefficient of 0.455, indicating that spending in this sector has not yet contributed to welfare improvement, while infrastructure expenditure records a positive coefficient of 0.492, demonstrating unexpected results and budget utilization inefficiencies. These findings suggest that policy strategies should prioritize education and economic strengthening, improve the effectiveness of health spending, and redesign infrastructure policies based on contextual regional needs to achieve equitable poverty reduction in Papua.